«Nos traen tan avasallados hasta quitarnos nuestro señorío»: cabildos mayas, control local y representación legal en el Yucatán del siglo XVI - Cunill, Caroline (Pontificia Universidad Católica del Perú. Fondo Editorial, 2016)
In Spanish Colonial America, as well as in the Iberian Peninsula at the same time, different jurisdictions intertwined in the same space. By way of consequence, the complex political organization of the New World was composed, at the local level, by the Indian and Spanish Councils, the doctrines, and the provincial structures called corregimientos. Although the officials of those institutions received precise instructions, in which the Spanish Crown defined and limited their functions, tensions were common between the Indian governors, the clergymen, the Spanish Councils’ officeholders, and the Spanish provincial magistrates, or corregidores. The present article will analyze a series of lawsuits that occurred in sixteenth century Yucatan and in which those authorities were implicated, in order to highlight not only the nature of the jurisdictional conflicts, but also the modalities of their resolution at stake in the Spanish Empire’s courts of justice. Special emphasis will be put on the jurisdiction of the Maya Councils with the objective of better understanding the scope of indigenous agency in Spanish Colonial America. We argue that the local control on the one hand, and the legal representation on the other, were key elements in these processes.

Al igual que en la península ibérica, en la América colonial se superpusieron distintas jurisdicciones en el mismo espacio, de modo que el complejo entramado político del Nuevo Mundo estaba conformado, a nivel local, por los cabildos indígenas y españoles, las doctrinas y los corregimientos. Aunque los representantes de aquellas instituciones recibieron detalladas instrucciones en las que la Corona española definía y limitaba sus funciones y prerrogativas, fueron frecuentes las tensiones entre los gobernadores indígenas, los alcaldes ordinarios, los curas beneficiados y los corregidores. A partir de una serie de pleitos en los que estuvieron involucradas estas autoridades, el presente trabajo analiza tanto la naturaleza de los conflictos jurisdiccionales que tuvieron lugar en el Yucatán del siglo XVI como las modalidades de su resolución en los foros de justicia de la Monarquía hispana. Se presta especial atención a la jurisdicción de los cabildos mayas con el fin de esclarecer el alcance de la participación indígena en el sistema político del Imperio hispánico. Consideramos que el control local, por un lado, y la representación legal, por otro, resultan fundamentales para comprender aquellos fenómenos.
Keywords: Historia; https://purl.org/pe-repo/ocde/ford#6.01.01